Fatigue and Its Related Factors in Pediatric and Adult Oncology Nurses - Rassouli M; Zandiye S; Noorian M; Zayeri F (Iran University of Medical Sciences, 2011)
Background & Aim: Pediatric and adult oncology wards have special characteristics which may lead to different levels of fatigue in nurses. The aim of this study was to compare fatigue and its related factors in pediatric and adult oncology nurses.   Materials & Methods: This descriptive comparative study was conducted with a sample of 215 nurses working in pediatric and adult oncology wards in selected educational hospitals of Tehran. Nurses were recruited by convenience sampling. Data was collected by "Questionnaire for Psychological & Social factors at work", "The Nursing Stress Scale", and "Oncology Nurses Fatigue Scale". Data analysis was performed using SPSS and T-test.   Results: There were significant statistical differences in all three dimensions of fatigue between the two groups of nurses (p<0.001). There were also a significant difference between the mean scores of emotional factors related to nurses' fatigue (p0.05).   Conclusion: Regarding the differences between emotional factors related to fatigue in pediatric and adult oncology nurses, it is recommended to pay more attention to the special features of pediatric and adult oncology wards that may lead to nurses' fatigue.